(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2015)
This article attempts to discuss the significance of architectural orders in contemporary architecture, by applying our conclusions to the design of the Centre of Contemporary Art (CarrÃ©e dâ€™Art) in Nimes, built by Norman Foster in 1993. This building, in the way it has been designed, encapsulates some basic questions surrounding the idea of order in architecture: from the classical orders of the Maison CarrÃ©e, to which it can be genetically compared, to its own design concept. In his design project, Norman Foster in effect employed in his design project the classical language of the historical monument and adapted it to the formal rules of contemporary architecture, showing that order is the development of a formal solution of an architectural organism. Â